Insight into SO4(-II)- dependent anaerobic methane oxidation in landfill: Dual-substrates dynamics model, microbial community, function and metabolic pathway. (15th March 2022) - Chi, Zifang; Zhu, Yuhuan; Yin, Ying
Graphical abstract: Highlights: Double-substrates model for SO4 2- driving anaerobic methane oxidation was established. Reverse methanogenesis was methane metabolism pathway in landfill. Methylotrophic methanogenesis was methanogenesis pathway in landfill. Methanobacterials, Methanosarcinales, Soil Crenarchaeotic were dominant. Abstract: In anaerobic landfill, SO4 2- could serve as electron receptor for methane oxidation. In theory, concentrations of both methane and SO4 2- should be related to methane oxidation rate. However, the dynamics process has yet to be discovered, and the understanding of metabolic pathways of the sulfate-dependent anaerobic methane oxidation (S-DAMO) process in landfill remains limited. In this study, S-DAMO dynamics was investigated by observing the CH4 oxidation rates under different CH4 / SO4 2- counter-gradients. The CH4 -SO4 2- dual-substrate model based on MichaeliseMenten equation was got (maximum substrate degradation rate Vmax [22.9 ± 1.31] µmol/[kg·d], half-saturation constants K m, C H 4 46.095 ± 0.41 p p m v, and K m, s o 4 2 - ( 7.26 ± 0.605 ) g / g ). High-throughput sequencing analysis indicated Methanobacterials, Methanosarcinales, and Soil Crenarchaeotic were the main functional microorganisms for S-DAMO in landfill. The metabolic pathway of S-DAMO was speculated as the reverse methanogenesis pathway through Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) analysis, while methanogenesis was the methyl nutrition way based on methanol. The enzymes related to the carbon and sulfur cycles and their relative abundances in the microcosms were analyzed to graph the methane metabolic pathway and the sulfur metabolic pathway. The findings provide important parameters for CH4 mitigation in landfills, and give a new insight for understanding S-DAMO metabolic pathway in landfill.